1986
DOI: 10.1113/jphysiol.1986.sp016340
|View full text |Cite
|
Sign up to set email alerts
|

A pseudo‐rebreathing technique for assessing the ventilatory response to carbon dioxide in cats.

Abstract: SUMMARY1. The ventilatory sensitivity to CO2 obtained from a non-steady-state step-ramp CO2 challenge (analogous to the Read rebreathing method) was compared with the one of the steady-state method.2. Experiments were performed during normoxia on twenty cats anaesthetized with chloralose-urethane. In eight of these cats additional measurements were carried out during metabolic acidosis and alkalosis.3. The slope of the non-steady-state ventilatory response curve to CO2 was not significantly different from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1

Year Published

1989
1989
2007
2007

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 10 publications
2
16
1
Order By: Relevance
“…This was the situation in our study. In fact, using the formula derived from the Berkenbosch et al (1986) model, we were able to account for about 80 % of the differences between SS and RB slopes that occurred in our study.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…This was the situation in our study. In fact, using the formula derived from the Berkenbosch et al (1986) model, we were able to account for about 80 % of the differences between SS and RB slopes that occurred in our study.…”
Section: Discussionmentioning
confidence: 84%
“…Recently, however, Berkenbosch et al (1986) examined the differences in the SS and RB technique using cats during normal STEADY-STATE AND REBREA THIVG METHODS conditions as well as during metabolic acidosis and alkalosis. In a second study they compared the two techniques in humans under normal conditions only (Berkenbosch et al 1989).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our opinion the dynamic end-tidal forcing (DEF) technique (Swanson & Bellville, 1975) In a previous study in anaesthetized cats (Berkenbosch et al 1986) we showed that the ventilatory response obtained by applying a step-ramp PETCO2 input could be satisfactorily described using the empirical two-compartment model introduced by Bellville, Whipp, Kaufman, Swanson, Aqleh & Wilberg (1979 (Teppema, Vis, Evers & Folgering, 1982;Eldridge, Kiley & Paydarfar, 1987) overwhelming the effect of changes in cerebral blood flow on the central time constant. Moreover, the anaesthetics used are expected to depress the responsiveness of cerebral vessels to hypercapnia (Levasseur & Kontos, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…To get some insight into the effect of changes in A and R on the non-steady-state CO2 sensitivity we performed experiments using a pseudo-rebreathing technique (Berkenbosch, DeGoede, Olievier & Schuitmaker, 1986). In a first approach we restricted ourselves to changing the step A, keeping R close to the values used by Read (1967).…”
Section: Introductionmentioning
confidence: 99%